REMOVAL OF TETRACYCLINE BY ADSORPTION ON NATURAL BENTONITE FROM AQUEOUS SOLUTIONS - Hashem, Zahraa; Hummadi, Khalid (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
Natural bentonite's potential as a sustainable solution for removing environmental contaminants makes it a promising candidate for addressing agricultural water quality challenges. This study evaluates whether natural bentonite can adsorb tetracycline (TC) from water-based solutions, offering a viable approach to improving water quality in agricultural settings. Under conditions of pH 7, 80 mg/L of tetracycline, 1 g/100 mL of natural bentonite, a 120-minute reaction period, 200 rpm of agitation, and a temperature of 25°C, the bentonite effectively adsorbed tetracycline. Analytical techniques, including Fourier-transform infrared (FTIR) spectroscopy, the Brunauer-Emmett-Teller (BET) method, and field emission scanning electron microscopy (FESEM), were used to characterize the bentonite, revealing a surface area of 37.13 m²/g. The isotherm study showed that the sorption of tetracycline onto NB fitted the Langmuir isotherm model with coefficient of determination (R2) equal to 0.961. Our findings underscore the applicability of natural bentonite for mitigating antibiotic contamination in wastewater.